A study of the flow boiling heat transfer in a minichannel for a heated wall with surface texture produced by vibration-assisted laser machining. Issue 3 (September 2016) - Piasecka, Magdalena; Strąk, Kinga; Maciejewska, Beata; Grabas, Bogusław
Abstract: The paper presents results concerning flow boiling heat transfer in a vertical minichannel with a depth of 1.7 mm and a width of 16 mm. The element responsible for heating FC-72, which flowed laminarly in the minichannel, was a plate with an enhanced surface. Two types of surface textures were considered. Both were produced by vibration-assisted laser machining. Infrared thermography was used to record changes in the temperature on the outer smooth side of the plate. Two-phase flow patterns were observed through a glass pane. The main aim of the study was to analyze how the two types of surface textures affect the heat transfer coefficient. A two-dimensional heat transfer approach was proposed to determine the local values of the heat transfer coefficient. The inverse problem for the heated wall was solved using a semi-analytical method based on the Trefftz functions. The results are presented as relationships between the heat transfer coefficient and the distance along the minichannel length and as boiling curves. The experimental data obtained for the two types of enhanced heated surfaces was compared with the results recorded for the smooth heated surface. The highest local values of the heat transfer coefficient were reported in the saturated boiling region for the plate with the type 1 texture produced by vibration-assisted laser machining.